Population Pharmacokinetics of Phenytoin Based on NONMEM in Patients with Intracranial Tumor During the First Week of Post-Craniotomy - Li, Zhong-dong; Liu, Meng; Li, Liang; Wan, Jing-hai; Lei, Zhaojin; Huang, Yong-an (Current Drug Metabolism, 2016)
Background: It was reported that phenytoin can prevent early post traumatic seizures. The present study aims to establish a population pharmacokinetic (PPK) model of oral phenytoin in patients with intracranial tumor during the early periods, the first week, of post-craniotomy to optimize phenytoin dosage regimen. Methods: Sixty-two patients with intracranial tumor were genotyped for CYP2C9 and CYP2C19 by real time PCR (TaqMan probe), and subsequently their phenytoin dosage regimens were designed according to the results of previous literature. A total of 123 plasma concentrations of oral phenytoin during the early periods of post-craniotomy, patient demographics, clinical biochemical indicators and drug combination were collected. A PPK model was performed using the nonlinear mixed effects model (NONMEM) program. Results: The final PPK model equations of oral phenytoin were found to be as follows: for patients with CYP2C9 *1/*1, Vmax=22.66x(BWT/60.96)0.454(mg/h) and Km =4.03 (mg/L); for patients with CYP2C9*1/*3, Vmax = 16.65x(BWT / 60.96 )0.454 (mg/h) and Km =5.96 (mg/L). The PPK model was proved to be stable and effective by bootstrap method. Clinical individualized dosage regimens of additional 50 patients were designed by above PPK model. Concentrations on the morning of Day 7 (D7 concentrations) of 56% (28/50) of these patients were within the therapeutic range (10 20mg/L), which demonstrated better improvement than that of 37.1% of above 62 patients. Conclusion: The final PPK model of oral phenytoin may be helpful to design phenytoin individualized dosage regimen at the early stage of post-craniotomy when characteristics of patients meet these of subpopulation in the study.
Keywords: NONMEM